O trabalho interprofissional nas equipes do núcleo ampliado de saúde da família e atenção básica em duas capitais brasileiras - Bravin, Pâmela Karine (2021)
Interprofessional work aims to overcome the hierarchy of collective work through democratic relationships and the sharing of objectives, identities and responsibilities. Primary Health Care (PHC) in brazilian unified health system, through the integrated arrangement between the teams of the Family Health Strategy (ESF) and those of the The Expanded Family Health and Basic Healthcare Centers (NASF-AB), is in an ideal scenario for consolidating interprofessional work. The NASF-AB, under the logic of matrix support, holds its space as a tool for transforming the curative and fragmented vision of care, through specialized assistance and technical-pedagogical support to ESF teams. This study aimed to analyze and compare the orientation for the interprofessional work of workers from the NASF-AB in two Brazilian capitals, João Pessoa (PB) and Campo Grande (MS). To this end, a cross-sectional study was carried out, with a structured questionnaire applied to a total of 182 professionals from the NASF-AB, which were 120 from João Pessoa and 62 from Campo Grande. The questionnaire was structured in three dimensions, the first referring to the general characterization of the interviewees, the second aimed at characterizing some aspects of the work process and related to interprofessional work and the third dimension was the Jefferson Scale of Attitudes Toward Interprofessional Collaboration (JeffSATIC). The results were divided into two scientific articles. The first article entitled “Characterization of the Expanded Family Health and Basic Healthcare Centers: a comparative study of two Brazilian capitals” corresponds to data obtained from the first two dimensions of the questionnaire. The results in this article showed that in the general sample, females were predominant (83%) and the mean age was 37.1±9.03 years. Professional training time was longer in Campo Grande (66.1% for more than 11 years) when compared to João Pessoa (65% for less than 11 years). About two-thirds of the overall sample (67%) had completed at least one lato sensu postgraduate course. Physiotherapists (25.3%), Psychologists (16.5%) and Nutritionists (16.5%) were most frequently observed in the general sample. However, in Campo Grande, Physical Education Professionals (14.5%) are more numerous than Nutritionists (12.9%) and Pediatricians (8.1%) and Gynecologists and obstetricians (9.7%) are observed, professions not found in João Pessoa. Professional Social Workers are present only in teams from João Pessoa and correspond to 13.3% of the categories in the municipality. The employment relationship in João Pessoa is mostly through temporary contracts (98.3%) while in Campo Grande most professionals follow the statutory regime (85.5%). In the general sample, the accumulated experience in the NASF-AB of the majority is up to five years (63.7%) and the relationship with the current team is less than two years (57.1%). As for the characteristics of the work process, most professionals in Campo Grande (42.6%) spend more time in their weekly schedule (51-75%) with collective care than in João Pessoa (31.5%, 26-50 % of weekly schedule). The same occurs with individual consultations, in which in Campo Grande 59% of professionals dedicate 26-50% of their weekly schedules, while in João Pessoa most of them (46.8%) claim to spend less time (0-25% ) of the workload.As for the development of activities with other professionals, there was a similar distribution of the percentage of 26-50% of the weekly working time dedicated both to the development of activities with professionals from their NASF-AB team (41.9%), and to those developed with the ESF teams (47.2%). In both capitals, most professionals (76.9%) satisfactorily assessed the team's interprofessional work and collaborative elements. In the second article entitled “Interprofessional work in the Expanded Centers for Family Health and Basic Health Care” there is an analysis of the data obtained from JeffSATIC. The average score of NASF-AB professionals at JeffSATIC was 118.63 (±10.12), with a median of 120 and a range from 77 to 140 points. In Campo Grande it was possible to observe that the professionals had a higher average (120.84±8.56) than that observed in João Pessoa (117.48±10.69). When related, the individual variables and the JeffSATIC scores did not imply statistical differences, but the highest medians were observed among female professionals, the youngest, those with less experience, longer with the team and in the category of Occupational Therapists. By comparing the data obtained through questionnaires applied to NASF-AB professionals in two Brazilian capitals, it was possible to identify common characteristics and specificities that fostered the production of knowledge about the organizational arrangement of the PHC with the inclusion of these teams. The high scores of professionals from the NASF-AB, close to the maximum expected at JeffSATIC, demonstrate that they appropriate interprofessional collaborative attitudes as guidelines for the work process in PHC. In this way, it reinforces the potential of NASF-AB teams in mobilizing changes in the traditional care paradigm and favoring the effectiveness of interprofessional work in PHC. The results of this research contribute to the recognition of the experience of these professionals, local managers and public policy makers, in defining strategies for permanent health education and training that lead to more collaborative skills in the exercise of work among teams in the PHC.